2018
DOI: 10.3390/atmos9090328
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quantitative Rainfall Prediction Using Ensemble Analogues in the Tropics: Case Study of Uganda

Abstract: Accurate and timely rainfall prediction enhances productivity and can aid proper planning in sectors such as agriculture, health, transport and water resources. However quantitative rainfall prediction is normally a challenge and for this reason, this study was conducted with an aim of improving rainfall prediction using ensemble methods. It first assessed the performance of six convective schemes (Kain–Fritsch (KF); Betts–Miller–Janjić (BMJ); Grell–Fretas (GF); Grell 3D ensemble (G3); New–Tiedke (NT) and Grel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The IDW is used in many studies that present spatially varying patterns e.g. [31] who used the IDW in modeling the spatial and temporal patterns of precipitation in Northwestern Uganda.…”
Section: Methodsmentioning
confidence: 99%
“…The IDW is used in many studies that present spatially varying patterns e.g. [31] who used the IDW in modeling the spatial and temporal patterns of precipitation in Northwestern Uganda.…”
Section: Methodsmentioning
confidence: 99%
“…Uganda is located within the latitudes: 1˚29'S to 4˚12'N and the longitudes: 29˚34'E to 35˚29'E [9] [10]. It is a landlocked country found in the eastern part of equatorial Africa [10] [12]. The country is relatively flat in the central with a few highland areas; and having mountains in the East (Mt.…”
Section: Study Areamentioning
confidence: 99%
“…Mugume et al . (), who used the analog approach to post‐process ensemble members who use different convection parametrization schemes, also explored the same idea. The authors demonstrated a root‐mean‐square error (RMSE) and bias reduction in rainfall prediction when using corresponding predictions of the (starting) ensemble mean analog as a forecast.…”
Section: Introduction: the Analogies As A Part Of A Weather Predictiomentioning
confidence: 99%
“…Following the work of Eckel and Delle Monache () and Mugume et al . (), the main goal of this study is to significantly improve the ALADIN‐LAEF ensemble 10 m wind speed forecast while maintaining low computational cost for the analog search. To test the performance of the analog‐based post‐processing and determine the optimal configuration, several experiments using different sources of information available to the ALADIN‐LAEF ensemble forecasts are performed.…”
Section: Introduction: the Analogies As A Part Of A Weather Predictiomentioning
confidence: 99%
See 1 more Smart Citation